COMPARISON OF ORAL (20 µG 2 HOURLY) VERSUS VAGINAL (25 µG 6 HOURLY) MISOPROSTOL FOR INDUCTION OF LABOUR IN TERM PREGNANCIES - Tahmina Yousaf (Army Medical College Rawalpindi, 2019)
Objective: To compare the outcome of oral misoprostol (20µg 2 hourly) with vaginal misoprostol (25µg 6hourly) for induction of labour in term pregnancies, in terms of frequency of vaginal delivery and cesarean section.